1979
DOI: 10.1007/bf00268282
|View full text |Cite
|
Sign up to set email alerts
|

The nature of transcription selectivity of bacteriophage SPO1-modified RNA polymerase

Abstract: Escherichia coli and Bacillus subtilis RNA polymerase have almost identical transcription specificities on bacteriophage SPO1 DNA when assayed in a coupled transcription-translation cell free system. SPO1-modified B. subtilis RNA polymerase has altered transcription specificity. It is shown that rifampicin-inhibited E. coli RNA polymerase can completely block transcription of SPO1 DNA by rifampicin resistant B. subtilis enzyme, whereas it has no effect on transcription by SPO1-modified B. subtilis RNA polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…It has been demonstrated that the E. coli-coupled transcription-translation system used in this study results in the production of specific phage proteins from SPO1 DNA (21,25). The endogenous E. coli RNA polymerase and the purified B. subtilis RNA polymerase specify the same SPOt early proteins when SPOt DNA is used as a template in this system (22) (Fig. 4, lanes I and J) and compete for initiation sites on the template DNA (22).…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…It has been demonstrated that the E. coli-coupled transcription-translation system used in this study results in the production of specific phage proteins from SPO1 DNA (21,25). The endogenous E. coli RNA polymerase and the purified B. subtilis RNA polymerase specify the same SPOt early proteins when SPOt DNA is used as a template in this system (22) (Fig. 4, lanes I and J) and compete for initiation sites on the template DNA (22).…”
mentioning
confidence: 73%
“…Preparation of RNA polymerase. RNA polymerase was prepared essentially according to Burgess and Jendrisak (2) as previously described (22). A Sephacryl S-200 column (3 by 30 cm) was included between the Polymin P (BASF Wyandotte Corp.) precipitation and DNA-cellulose chromatography as a sizing and desalting step.…”
Section: Geiduschek and S Okubomentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo synthesis of SPOl middle RNA classes requires the modification of host RNA polymerase by the product of SPOl early gene 28 (gp28) (7). In vitro, we have used an E. coli-coupled transcription-translation cfs to study SPOl gene expression by placing SPOl RNA synthesis under the control of purified B. subtilis RNA polymerase isolated from uninfected or SPOl-infected rifampin-resistant cells (21). The procedure involves preincubation of SPOl DNA with Rif' B. subtilis RNA polymerase.…”
Section: Resultsmentioning
confidence: 99%